Inhibitory Test Of Citronella Essential Oil (Cymbopogon Nardus L. Rendle) Againts Aspergillus Flavus Growth: INHIBITORY TEST OF CITRONELLA ESSENTIAL OIL - Rahmat Pannyiwi; Menik Kasiyati; Martha Atik Martiningsih; Siti Nur Syariah; Suyana Suyana; Rita Rena Pudyastuti; Sujono Sujono (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Indonesia is the one of tropical climate country with high air humidity. It becomes the main factor of fungal infection, that is called otomycosis, which is caused by Aspergillus flavus. The treatment of otomycosis is usually done by giving an azole antifungal drugs that can give the beneficial and adverse effects. Treatment of otomycosis can be done with various kinds of herbs. One of herbs that is used, it is citronella. Citronella contains essential oil 0,4% and in citronella essential oil contains citronellal 32-45% and geraniol 12-15% has ability as an antifungal. The aim of this study is to determine the inhibitory of citronella essential oil against Aspergillus flavus growth. Methods: The type of this research is laboratory experiments with posttest only with control group design.  24-hour Aspergillus flavus is used as the research subjects which had been inoculated on SDA media and given essential oils in various concentrations of 0.5%, 1.0%, 1.5%, 2.0 %. The observation of citronella essential oil inhibitory as an antifungal by measuring the diameter of inhibitory zone, it uses a caliper. Results: The measuring from average diameter of Aspergillus flavus fungal growth zone in each concentration, they are 0.5% ;1.0%; 1.5%; 2.0% is 9.11 mm; 12.03 mm; 13.62 mm; 16.81 mm. The higher concentration of essential oil, it makes the wider diameter of the inhibition zone. The level of sensitivity is intermediate, sensitive, sensitive, sensitive. The level of effectiveness is less effective, effective enough, effective, very effective. The results of statistical analysis showed that citronella essential oil has the inhibitory against Aspergillus flavus growth. Conclusion: this study was various concentration of citronella essential oil have a significanteffect on the growth of inhibitory Aspergillus flavus.